1998
DOI: 10.1051/limn/1998011
|View full text |Cite
|
Sign up to set email alerts
|

Hyporheic biofilm development on artificial substrata, as a tool for assessing trophic status of aquatic systems : first results

Abstract: To determine the relationship between biofilm characteristics and organic nutrient content, we investigated the development of hyporheic biofilms on artificial substrata (glass slides) in the early phase of bacterial colonization (one week) in contrasting river habitats with significantly different concentrations of dissolved organic carbon (DOC) and biodegradable and refractory DOC (BDOC and RDOC). Results suggest that the quality of DOC (i.e. BDOC versus RDOC content) controlled electron -transport system (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Viability can be assessed either at the cellular level to assess specific aspects of bacterial cell physiology or metabolism (Barer & Harwood, 1999;Bogosian & Bourneuf, 2001), or at the community level to evaluate the fitness of pluri-specific consortia and to estimate the active biomass fraction (Claret, 1998;Haglund et al, 2002;Luna et al, 2002;Sherr et al, 2002;Araya et al, 2003;Schumann et al, 2003;Tam et al, 2003). Membrane integrity, as an indicator of viability, was reported to remain several hours after lethal treatment although re-growth of injured cells is unlikely to occur unless cellular integrity is maintained (Villarino et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Viability can be assessed either at the cellular level to assess specific aspects of bacterial cell physiology or metabolism (Barer & Harwood, 1999;Bogosian & Bourneuf, 2001), or at the community level to evaluate the fitness of pluri-specific consortia and to estimate the active biomass fraction (Claret, 1998;Haglund et al, 2002;Luna et al, 2002;Sherr et al, 2002;Araya et al, 2003;Schumann et al, 2003;Tam et al, 2003). Membrane integrity, as an indicator of viability, was reported to remain several hours after lethal treatment although re-growth of injured cells is unlikely to occur unless cellular integrity is maintained (Villarino et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that metabolic activity in the hyporheic zone depends on the quality and quantity of organic carbon (Brugger et al, 2001;Craft et al, 2002;Crenshaw et al, 2002). Dissolved organic carbon (DOC) is considered as the main source of carbon for hyporheic microorganisms (Claret et al, 1997;Claret, 1998a). The quality of DOC (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of DOC (i.e. biodegradable versus refractory DOC content) has been shown to control ETS-active bacterial abundances early in colonisation of artificial substrata, while DOC concentrations limit biofilm development only in the latter phase of colonisation (Claret, 1998a). Higher contents of labile autochthonous organic matter cause higher microbial respiratory activity, reflected in higher ETS activity and oxygen consumption rate (Muri & Simčič, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The sonicated subsamples were diluted (usually 100 times for coarse fraction and 1000 times for fine fraction). Two ml of sonicated and diluted subsample were stained with DAPI solution (final concentration 5 µg ml -1 ) for 5 min at room temperature (CLARET, 1998). After incubation, the suspension was filtered onto membrane (Millipore HTBP, pore size 0.2 µm) that was mounted in immersion oil and examined under an epifluorescence microscope (Olympus BX 60).…”
Section: Sample Processingmentioning
confidence: 99%
“…This could partly be explained by the heterogeneity of hyporheic sediments together with the practical difficulties of proper sampling of such a complex habitat (FISCHER et al, 1996). To avoid this problem, artificial substrates were used in several studies of the hyporheic biofilm (BÄR-LOCHER and MURDOCH, 1989;CLARET, 1998). FISCHER et al (1996) quantified bacterial abundance, biomass and activity on standardised sediment particles.…”
Section: Introductionmentioning
confidence: 99%